Legal Measures Regarding Rehabilitation of Small and Medium-Sized Enterprises (SMEs) - Mahavinijchaimontri, Pratya; Janpradab, Sumate; Moolsilpa, Poom; Kangrang, Anongrit (Ph.D. in Social Sciences Journal, 2020)
In this research, the researchers have objectives to (1) Study the background and problems of the rehabilitation of small and medium-sized enterprise in Thailand (2) Comparatively analyze the laws regarding the rehabilitation of small and medium-sized enterprises of Thailand and the law on business rehabilitation of foreign countries. And (3) propose more effective legal measures related to the rehabilitation of small and medium-sized enterprises. The researchers used the qualitative research methodology by using 3 methods of data collection, namely document research, in-depth interviews of 101 people and focus group discussion of 43 people, and analyzed the data by using content analysis techniques and comparison. Findings are follows: The results of the research showed that small and medium-sized enterprises are an important factor in driving the country’s economy. But the Bankruptcy Act, A.D. 1940. did not allow small and medium-sized enterprises that experience temporary liquidity problems to enter the business rehabilitation process easily, fairly, conveniently, quickly, flexibly, economically, which could help all small and medium enterprises. When compared with foreign laws, the Bankruptcy Act, A.D. 1940. provisions should be revised at the entering business rehabilitation process, proceedings and the process for managing the rehabilitation plan stages to help entrepreneurs.